Comprehensive structural and functional analyses of RAD50 nsSNPs: from prediction to impact assessment - Malik, Samina; Jawad Ul Hasnain, Mirza; Zaib, Gul; Saadia, Haleema; Malik, Arif; Zahid, Ayesha (Frontiers in Bioinformatics, 2025)
BackgroundThe RAD50 gene on chromosome 5q3.11 plays an important role in the MRN (Mre11–Rad50–Nbs1) complex. This complex orchestrates cellular responses to the DNA double-strand breaks (DSBs) through several pathways for genome stability. This study aims to investigate the functional impact of non-synonymous single-nucleotide polymorphisms (nsSNPs) in RAD50 (a breast cancer-associated gene) and focuses on their consequences on protein structure and interaction within the MRN complex.MethodsA total of 1,806 nsSNPs were retrieved and subjected to variant analysis using a set of computational tools and ConSurf. Pathogenicity and protein stability criteria were established based on specific tools. Highly conserved damaging nsSNPs were prioritized for the structural analysis. GOR-IV was used for secondary structure prediction, whereas AlphaFold, RoseTTAFold, and I-TASSER were used for protein structure prediction. The docking of RAD50–Mre11A complexes was performed using HADDOCK to assess the impact of nsSNPs on protein–protein interactions. Molecular dynamic simulation was performed to verify the role of mutants in molecular docking analysis.ResultsA subset of pathogenic and disease-associated nsSNPs in the RAD50 gene altered the protein stability and interactions with the Mre11A protein. Substantial alterations in the interacting profiles of mutants (A73P, V117F, L518P, L1092R, N1144S, and A1209T) suggest potential implications for DNA repair mechanisms and genome stability.ConclusionThe study discloses the normative impact of RAD50 mutations on the pathophysiology of breast cancer. It can provide the basis to treat RAD50 mutation-deficient cells.